Finding your right (or left) partner to merge - Ronny Freier; Benjamin Bruns; Abel Schumann (European Regional Science Association (ERSA), 2015)
We study political determinants of municipality amalgamations during a boundary reform in the German state of Brandenburg, which reduced the number of municipalities from 1,489 to 421. The analysis is conducted using an extensive data set on the political decision makers as well as fiscal and socio-economic variables on the level of the individual municipality and on the level of individual mergers. We ask whether party representation in the town council influences the merger decision. To identify the effect, we follow a dual approach and make use of different stages in the reform process. First, municipalities were initially free to choose partners. In a later phase of the reform the state legislature forced municipalities to amalgamate. We can, thus, compare voluntary to forced units. Second, we simulate potential mergers from the map of municipalities and compare voluntary mergers to those simulated units. Both approaches show that political representation mattered significantly during the voluntary stage of the merger reform.
Keywords: H11; H10; 330